Cloning of a novel tetrahydrofolate-dependent dicamba demethylase gene from dicamba-degrading consortium and characterization of the gene product - Li, Na; Chen, Le; Chen, E.; Yuan, Cansheng; Zhang, Hao; He, Jian (Frontiers in Microbiology, 2022)
Dicamba, an important hormone-type systemic herbicide, is widely used to control more than 200 kinds of broadleaf weeds in agriculture. Due to its broad-spectrum, high efficiency and effectively killing glyphosate-resistant weeds, dicamba is considered as an excellent target herbicide for the engineering of herbicide-resistant crops. In this study, an efficient dicamba-degrading microbial consortium was enriched from soil collected from the outfall of a pesticide factory. The enriched consortium could almost completely degrade 500 mg/L of dicamba within 12 h of incubation. A novel tetrahydrofolate (THF)-dependent dicamba demethylase gene, named dmt06, was cloned from the total DNA of the enriched consortium. Dmt06 shared the highest identity (72.3%) with dicamba demethylase Dmt50 from Rhizorhabdus dicambivorans Ndbn-20. Dmt06 was expressed in Escherichia coli BL21 and purified to homogeneity using Co2+-charged nitrilotriacetic acid affinity chromatography. The purified Dmt06 catalyzed the transfer of methyl from dicamba to THF, generating the herbicidally inactive metabolite 3,6-dichlorosalicylate (3,6-DCSA) and 5-methyl-THF. The optimum pH and temperature for Dmt06 were detected to be 7.4 and 35°C, respectively. Under the optimal condition, the specific activity of Dmt06 reached 165 nmol/min/mg toward dicamba, which was much higher than that of Dmt and Dmt50. In conclusion, this study cloned a novel gene, dmt06, encoding an efficient THF-dependent dicamba demethylase, which was a good candidate for dicamba-resistant transgenic engineering.